Structured Neonatal Point-of-Care Ultrasound Training Program - Kurepa, Dalibor; Boyar, Vitalya; Zaghloul, Nahla; Beachy, Joanna; Zaytseva, Alla; Teng, David; Cooper, Rubin; Klewer, Scott; Amodio, John (American Journal of Perinatology, 2020)
Objective Point-of-care ultrasound (POC US) has been increasingly used by intensive care physicians. Growing use of POC US necessitates defining distinct clinical indications for its application, as well as structured POC US training programs. Homogeneous approach to POC US education combined with rigorous quality assurance should further enable POC US to become standard-of-care clinical tool. This study aimed to present the first, innovative, and structured POC US program in neonatal–perinatal medicine field. In addition, we reviewed the availability of the POC US training programs across different medical specialties.Study Design Available English-language publications on POC US training programs in general and neonatal–perinatal medicine were reviewed in this study.Discussion Mounting body of evidence suggests improved procedural completion rates, as well as clinical decision making with the use of POC US. However, limited research supported the existence of structured, comprehensive POC US programs. It was recognized that medical institutions need to develop syllabuses, teach, and credential increasing number of health care professionals in the use of POC US. We defined intuitive educational strategy that encompasses POC US clinical indications, educational curriculum, scanning protocols, competence evaluation, and finally credentialing process. In addition, we offered description of the imaging quality assurance, as well as POC US coding, and reimbursement.Conclusion Future efforts need to be dedicated to the ongoing development of neonatal POC US as a clinical instrument. It should allow for eventual paradigm change and improved effectiveness in management of critically ill neonates.
Keywords: ultrasound; point-of-care; training program; neonatology